Anti-Essentialism and Intersectionality - Grillo, Tina (Theorizing feminisms a reader, 2006)
'What is oppression ?' 'What should be done about it ?' Organized around these questions, Theorizing feminisms : a reader provides an overview of theoritical feminist writing about the quest for gender justice. Incorporating both classic and cutting-edge material, the reader takes into account the full diversity of women, highlighting the effects of race, ethnicity, nationality, class, sexuality, and religion on women's experience. Theorizing feminisms is organized into four sections and includes fifty-four essays. The first section introduces several basic concepts commonly employed when thinking about sexism - oppression, social construction, essentialism, intersectionality, gender, race, and class - and also raises questions about the perspective and legitimacy of the theorist. The second section surveys three approaches that attempt to characterize in a general way the source of injustice toward women : humanist feminism ('the sameness approach'), gynocentric feminism ('the difference approach'), and dominance feminism. Offering an alternate perspective, the third section introduces two 'localizing' approaches, grounded in postmodernism and identity politics, respectively. Skeptical of theories that attempt to analyze social phenomena across history and culture, authors in this section challenge, rather than answer, the text's organizing questions. The final section explores the relationship of feminism theory to three liberatory projects - postcolonialism, neo-materialism, and queer theory - that do not characterize themselves as feminist, yet take gender as a significant category of analysis. Each section opens with an introduction and each essay is followed by helpful study questions. the majority of the essays are presented in their entirety. Theorizing feminisms underscores the strong connection between feminist theory and practice by including essays that illustrate important political inspirations or applications of each theoritical approach. It also presents versions of the same approach from various points in history, revealing feminist theory to be dynamic and evolving, rather than static. Ideal for interdisciplinary courses in feminist theory, this volume will also serve as an invaluable reference for current and future generations of theorists."
Section: 1 vol. (XIX-564 p.) ; 24 x 19 cm
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; cours; discipline; essentialisme; intersectionnalité; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; thématiques; théorie féministe

La sexualité entre sexisme et racisme: les descendantes de migrant·e·s du Maghreb et la virginité - Hamel, Christelle (Nouvelles Questions Féministes, 2006)
L'article présente le résultat d'une recherche sur la vie affective et sexuelle des jeunes Français-es descendant de migrant-e-s originaires du Maghreb, qui décrit comment les jeunes femmes se positionnent par rapport au principe de virginité. Alors que cette norme est un mode de contrôle de la sexualité des femmes, certaines le revendiquent, tandis que celles qui l'ont transgressé expriment combien cette décision leur fut difficile. Pour comprendre la prégnance de leur attachement à la valeur de la virginité, l'autrice replace leurs discours et pratiques dans le contexte social qui les a fait naître. Elle décrit donc comment les discriminations et la stigmatisation racistes façonnent l'expérience de vie de ces jeunes femmes et montre combien cette expérience du racisme se combine à l'expérience du sexisme dans les familles et dans la société globale. Ici, l'imbrication du sexisme et du racisme fait peser sur elles un système de contraintes complexe qui les soumet à des injonctions paradoxales. Ce n'est qu'au regard de ces injonctions que la revendication par certaines de cette norme qui par ailleurs les opprime devient intelligible.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; afrique; approches et analyses; corps; cours; discipline; europe; france; histoire et politique; intersectionnalité; maghreb; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexisme; sexualité; sociologie; systèmes d'oppressions; thématiques; virginité; études démographiques

Arab American Femininities: Beyond Arab Virgin/ American(ized) Whore - Naber, Nadine (Feminist Studies, 2006)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; anthropologie culturelle; approches et analyses; arabes-américaines; cours; discipline; discours dominant; femmes* arabes; féminisme islamique; histoire et politique; identités culturelles; intersectionnalité; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; système colonial; systèmes d'oppressions; thématiques; états-unis

The Politics of Protection: Body Image, Social Pressures, and the Misrepresentation of Young Black Women - Poran, Maya A. (Sex Roles : A Journal of Research, 2006)
As part of a larger multi-method study, 15 Black women college students participated in focus group discussions on the body. Contrary to popular theories that propose that Black women are protected by a “Black Culture” that buffers them from negative effects of body representations—thereby leaving them with higher body esteem—the themes that emerged in the focus group discussions indicate that young Black women are indeed feeling (1) pressures to be thin, (2) pressures from the preferences of men of diverse ethnicities, (3) competition with other Black women in the realms of beauty, and (4) a strong sense of being misrepresented by media images of thin Black women. These results not only indicate that body image issues are of real pressing concern to young Black women, but that psychological research methodologies may be adding to the misrepresentation of young Black women and their struggles. Qualitative methods must be utilized in order to hear more clearly the voices of Women of Color.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; image corporelle; intersectionnalité; new york; premier cycle; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; états-unis

Unveiled Sentiments: Gendered Islamophobia and Experiences of Veiling among Muslim Girls in a Canadian Islamic School - Zine, Jasmin (Equity & Excellence in Education, 2006)
The practice of veiling has made Muslim women subject to dual oppressions–racism and Islamophobia–in society at large and patriarchal oppression and sexism from within their communities. Based on a narrative analysis of the politics of veiling in schools and society, the voices of young Muslim women attending a Canadian Islamic school speak to the contested notion of gender identity in Islam. The narratives situate their various articulations of Islamic womanhood in ways that both affirm and challenge traditional religious notions. At the same time they also are subject to Orientalist representations of veiled and burqa clad women that represent them as oppressed and backward. Focusing on ethnographic accounts of veiling among Muslims girls who attended a gender-segregated Islamic high school in Toronto, this discussion allows a deeper understanding of how gendered religious identities are constructed in the schooling experiences of these Muslim youth. (Contains 11 notes.)
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; corps; cours; discipline; féminisme islamique; intersectionnalité; islamophobie; ontario; patriarcat; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences de l'éducation; sex2283; sexisme; systèmes d'oppressions; thématiques; toronto; voiles islamiques